An Imidazoline 2 Receptor Ligand Relaxes Mouse Aorta via Off-Target Mechanisms Resistant to Aging - Jiménez-Altayó, Francesc; Cabrera, Anna; Bagán, Andrea; Giménez-Llort, Lydia; D’Ocon, Pilar; Pérez, Belén; Pallàs, Mercè; Escolano, Carmen (Frontiers in Pharmacology, 2022)
Imidazoline receptors (IR) are classified into three receptor subtypes (I1R, I2R, and I3R) and previous studies showed that regulation of I2R signaling has neuroprotective potential. In order to know if I2R has a role in modulating vascular tone in health and disease, we evaluated the putative vasoactive effects of two recently synthesized I2R ligands, diethyl (1RS,3aSR,6aSR)-5-(3-chloro-4-fluorophenyl)-4,6-dioxo-1-phenyl-1,3a,4,5,6,6a-hexahydropyrrolo[3,4-c]pyrrole-1-phosphonate (B06) and diethyl [(1-(3-chloro-4-fluorobenzyl)-5,5-dimethyl-4-phenyl-4,5-dihydro-1H-imidazol-4-yl]phosphonate] (MCR5). Thoracic aortas from Oncins France 1 (3- to 4-months-old) and C57BL/6 (3- to 4- and 16- to 17-months-old mice) were mounted in tissue baths to measure isometric tension. In young mice of both strains, MCR5 induced greater relaxations than either B06 or the high-affinity I2R selective ligand 2-(2-benzofuranyl)-2-imidazoline (2-BFI), which evoked marginal responses. MCR5 relaxations were independent of I2R, as IR ligands did not significantly affect them, involved activation of smooth muscle KATP channels and inhibition of L-type voltage-gated Ca2+ channels, and were only slightly modulated by endothelium-derived nitric oxide (negatively) and prostacyclin (positively). Notably, despite the presence of endothelial dysfunction in old mice, MCR5 relaxations were preserved. In conclusion, the present study provides evidence against a functional contribution of I2R in the modulation of vascular tone in the mouse aorta. Moreover, the I2R ligand MCR5 is an endothelium-independent vasodilator that acts largely via I2R-independent pathways and is resistant to aging. We propose MCR5 as a candidate drug for the management of vascular disease in the elderly.